Brain waves in response to Quran and Dhikir - Norsiah, Fauzan; Siti Naqiah, Shahidan (Universiti Sains Islam Malaysia 2015, 2015)
The purpose of the study was to identify the differences that occur in the brain (the region of interest, ROI) while reciting and listening to Dhikr & Al-Quran, such as "Astaghfirullah”, Subhan Allah, Allahmulillah, Lailaha - illa Allah - huakbar". 10 students were involved voluntarily for the resesarch. Brain waves were recorded from the subject based on 10-20 using 19 qEEG Mitsar current channel subjects of reciting and listening. Based on statistical analysis contained in the details, test results paired t test to both hypotheses found there was no significant difference between cognitive activity such as reciting and hearing. The results of the analysis revealed that the dominant wave was Delta, followed by Theta waves. (113 words)